AN EXPLORATORY STUDY ON WORKING CAPITAL MANAGEMENT AMONG PETTY TRADERS IN KUALA NERANG, KEDAH - Hamat, Zahri; Malek, Nor Malina; Suet Leng, Khoo; S. Gopal, Parthiban; Husain, Aiman Syazwan (Journal of Human Capital Development (JHCD), 2014)
Petty trading is a common economic activity amongst locals in Kuala Nerang, Kedah. Currently, an ironic situation exists where the petty traders in Kuala Nerang claim that their businesses are profitable yet they still face a deficiency in working capital. To explore the situation, this working paper aims to identify the reasons behind the high instances of working capital deficiency amongst the petty traders. To this end, the following research questions are raised. Why does this problem occur? Do the petty traders actually suffer a loss in their businesses? Do they keep their accounting records properly to enable them to ascertain whether their businesses generated a profit or suffered a loss? The findings reported in this paper are based on in-depth interviews drawn from a convenience sample of 20 petty traders in Kuala Nerang. It was revealed that accounting records are not kept in order, and therefore, the profits made cannot be determined accurately. This could be due to a lack of understanding on working capital management among the petty traders. Hence, it is not unusual for them to encounter a shortage in working capital. Keywords: petty traders, working capital, accounting records, rural informal sector, Kuala Nerang